Marketing interno como factor de la cultura de innovación en las pequeñas y medianas empresas. - Dallane Antonela Gómez Saldaña; Miriam Cubas; José Joel Cruz-Tarrillo; Robin Alexander Díaz Saavedra (My University, 2023)
The various events that have occurred in the last five years have allowed companies to undergo a transformation in order to maintain their relevance and relevance, the purpose of this research is to determine the influence of internal marketing on the culture of innovation. For the achievement of this objective, the investigation adopted a cross-sectional methodological perspective, the sample was constituted by 380 participants to whom the scale of internal marketing and innovation culture was applied. The results obtained show that development, recruitment and internal communication are predictors of innovation culture. Likewise, a moderate and statistically significant relationship is shown between the two variables. It is concluded that the predominance of internal marketing components predicts a culture of innovation in its different pillars.
Keywords: Relevance (law); Internal marketing; Sample (material); Order (exchange); Political science; Business administration; Business; Scale (ratio); Welfare economics; Latin Americans; Organizational culture; Sociology; Marketing; Humanities; Relevance (law); Internal marketing; Sample (material); Order (exchange); Scale (ratio); Social Sciences Business, Management and Accounting Organizational Behavior and Human Resource Management Educational and Organizational Development; Social Sciences Economics, Econometrics and Finance Economics and Econometrics Business, Innovation, and Economy; Social Sciences Social Sciences Sociology and Political Science Diverse Applied Research Studies